Price Transparency, Perceived Risk, and Consumer Trust in Cross-Border E-Commerce: A Systematic Literature Review - Deny Ariyanto; Maria Cristiana Iman Kalis; Muhammad Irfani Hendri (Information Technology and Science (ITScience), 2026)
Cross-border e-commerce has become an important component of the global digital economy, enabling consumers to engage in international online transactions while simultaneously facing challenges related to information asymmetry, perceived risk, and trust. This study aims to synthesize existing literature on the relationships among price transparency, perceived risk, and consumer trust in cross-border e-commerce. A Systematic Literature Review (SLR) was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles were retrieved from the Scopus database using keywords related to price transparency, perceived transaction, perceived risk, trust, and cross-border e-commerce. From an initial pool of 476 articles, 45 studies met the inclusion criteria and were analyzed through thematic analysis supported by the Watase Uake System. The findings reveal that price transparency, consumer trust, and perceived risk are the dominant themes shaping consumer behavior in cross-border digital marketplaces. Price transparency plays a critical role in reducing information asymmetry and enhancing consumer confidence, while trust acts as a key mechanism for mitigating uncertainty in international online transactions. The review also highlights the growing importance of emerging technologies, including artificial intelligence (AI), blockchain, and augmented reality (AR), in strengthening transparency, security, and transaction efficiency. Furthermore, the literature is primarily grounded in Information Asymmetry Theory, Theory of Planned Behavior, Signaling Theory, and Structural Equation Modeling approaches. This study concludes that transparent pricing practices and trust-enhancing digital environments are essential for sustainable cross-border e-commerce development and recommends further research focusing on developing countries, cross-cultural contexts, and technology-driven trust mechanisms.